Corporate social and environmental responsibility in the face of environmental disasters in Maceió caused by Braskem: from the environmental licensing inspection process to the prevention principle - Godoi, Carlos Eduardo Martins de; Ventura, Luciana (JRG Journal of Academic Studies, 2024)
The study deals with the socio-environmental responsibility of the company Braskem with regard to environmental disasters in Maceió, focusing on the exploitation of rock salt and the consequences left for local communities. Therefore, it investigates the application of the principle of environmental prevention, seeking to identify failures in compliance with this principle, which resulted in significant damage to infrastructure, the environment and the lives of affected residents. Identify that, due to the lack of supervision and preventive measures, the situation described emerged with the sinking of the soil, the displacement of thousands of people and the loss of local biodiversity. The study reinforces that socio-environmental responsibility is not limited to legal obligations, but ethics are vital components for the safety and development of the community. It is concluded that Braskem's failure to implement preventive plans and investigation responsibilities left the local population in a very precarious social and environmental situation, reinforcing the need for stricter public policies and effective supervision. Further studies are needed to examine the impact of affected areas and the long-term effect and how effective their compensatory measures are.